Parent's Perspective on Homeschooling: A Review Paper (International Journal of Innovative Research in Engineering & Management, 2021)
Over the last ten years, the popularity of  homeschooling has skyrocketed. This group includes  brilliant and talented kids, yet despite this expansion, the  research literature has not increased much. Investigators questioned 13 parents of talented homeschooled children  to get a better understanding of the smart homeschooling  family. The data revealed four main themes: (a) parents are  the experts, (b) isolation, (c) difficulties, and (d) intimate roles. These parents only chose to homeschool after  repeated efforts to collaborate with the public school, and  the women held the main responsibility for homeschooling  in these households, according to the findings. Though the  transition to homeschooling eased many of the problems  that these families had in public school, it also presented a  new set of obstacles. This exploratory research aims to  learn more about why parents of talented children choose  to homeschool their children.
Keywords: Education Method; Gifted Quality; Grounded Theory; Homeschooling